2015
DOI: 10.1039/c4ra16761a
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of acid strength effect on ibuprofen adsorption and release by aluminated mesoporous silica nanoparticles

Abstract: Mesoporous silica nanoparticles (MSN) with 1-10 wt% loading of aluminum (Al) were prepared and characterized by XRD, N 2 physisorption, 29 Si and 27 Al NMR, FT-IR and FT-IR preadsorbed pyridine. All samples were evaluated for ibuprofen adsorption and release. The results showed that MSN gave almost complete ibuprofen adsorption while the addition of 1, 5, and 10 wt% Al onto MSN (1Al-MSN, 5Al-MSN and 10Al-MSN) resulted in 35%, 58%, and 79% of adsorption, respectively. The characterization results elucidated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 45 publications
(111 reference statements)
1
19
0
Order By: Relevance
“…After the adsorption of ibuprofen, we found that the peak corresponding to (Fe, Si)-OH/C-O-C had shifted, which was related to the formation of hydrogen bonds between the -OH groups of inorganic materials on the MAP and the -COOH groups of ibuprofen. This finding was consistent with other reports, in which hydrogen bonding was considered the interaction between PPCPs and adsorbents [34][35][36][37][38] . www.nature.com/scientificreports www.nature.com/scientificreports/ Adsorption isotherms.…”
Section: Resultssupporting
confidence: 93%
“…After the adsorption of ibuprofen, we found that the peak corresponding to (Fe, Si)-OH/C-O-C had shifted, which was related to the formation of hydrogen bonds between the -OH groups of inorganic materials on the MAP and the -COOH groups of ibuprofen. This finding was consistent with other reports, in which hydrogen bonding was considered the interaction between PPCPs and adsorbents [34][35][36][37][38] . www.nature.com/scientificreports www.nature.com/scientificreports/ Adsorption isotherms.…”
Section: Resultssupporting
confidence: 93%
“…3 Fourier transform infrared (FTIR) measurements were carried out using an Agilent Carry 640 FTIR Spectrometer. The catalyst was prepared as a self-supported wafer and activated under vacuum at 673 K for 3 h. 15 UV-vis spectra were obtained on a Thermo Spectronic spectrophotometer model Genesys 10UV, from 300-700 nm using a 1 cm quartz cuvette.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…The mechanism of adsorption of IP on the polymeric network is currently under investigation and no clear-cut conclusion can be metioned at this stage. However, in analogy to recently reported research on the adsorption of IP in mesomorphous materials, a possible role of hydrogen-bonding between carboxylate group of IP and the hydroxyl groups present in the agarose units could be invoked 63 . Accordingly, the attractive polymer-IP interactions would provide the driving force to overcome the electrostatic repulsion between the negatively charged polymer sites and the ionized carboxylic groups of monomeric IP.…”
Section: Modeling Ip Diffusion Coefficients In Gelmentioning
confidence: 99%